2023
DOI: 10.1038/s41467-023-38188-z
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of SARS-CoV-2 Omicron subvariants leading to the emergence of BQ.1.1 variant

Abstract: In late 2022, various Omicron subvariants emerged and cocirculated worldwide. These variants convergently acquired amino acid substitutions at critical residues in the spike protein, including residues R346, K444, L452, N460, and F486. Here, we characterize the convergent evolution of Omicron subvariants and the properties of one recent lineage of concern, BQ.1.1. Our phylogenetic analysis suggests that these five substitutions are recurrently acquired, particularly in younger Omicron lineages. Epidemic dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 78 publications
10
101
0
Order By: Relevance
“…BQ.1.1 subvariant bears all five recent convergent mutations (R346T, K444T, L452R, N460K, and F486V). Evolutionary studies suggested that sublineages descending from BA.5, including BQ.1 and BQ.1.1 convergently increased viral fitness by consecutively acquiring substitutions at the R346, N460, and K444 residues, and it was proposed that BQ.1.1 increased the binding affinity to human ACE2 during evolution from the BA.5 variant . Consistent with previous studies from the same group , L452R and N460K substitution can increase the ACE2 binding affinity, while K444T substitution significantly decreased ACE2 binding affinity .…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…BQ.1.1 subvariant bears all five recent convergent mutations (R346T, K444T, L452R, N460K, and F486V). Evolutionary studies suggested that sublineages descending from BA.5, including BQ.1 and BQ.1.1 convergently increased viral fitness by consecutively acquiring substitutions at the R346, N460, and K444 residues, and it was proposed that BQ.1.1 increased the binding affinity to human ACE2 during evolution from the BA.5 variant . Consistent with previous studies from the same group , L452R and N460K substitution can increase the ACE2 binding affinity, while K444T substitution significantly decreased ACE2 binding affinity .…”
Section: Introductionsupporting
confidence: 78%
“…Evolutionary studies suggested that sublineages descending from BA.5, including BQ.1 and BQ.1.1 convergently increased viral fitness by consecutively acquiring substitutions at the R346, N460, and K444 residues, and it was proposed that BQ.1.1 increased the binding affinity to human ACE2 during evolution from the BA.5 variant . Consistent with previous studies from the same group , L452R and N460K substitution can increase the ACE2 binding affinity, while K444T substitution significantly decreased ACE2 binding affinity . It was suggested that acquiring L452R and N460K substitutions that potentially increase ACE2 binding ability can allow for the increased substitution frequency at the convergent sites to modulate immune escape capacity.…”
Section: Introductionsupporting
confidence: 71%
“…285 Derived from variant BA.5, RBD of BQ.1.1 has lower dissociation constant with ACE2 ( K D = 0.66 ± 0.11 nM) than BA.5 ( K D = 108 ± 0.16 nM) using yeast surface display assay. 286 However, the full spike proteins of BA.5 (0.61 nM), BQ.1 (0.62 nM), and BQ.1.1 (0.56 nM) have equivalent binding affinities. 22 Subvariant BQ.1.1 has mutations R346T and N460K that improve binding to human ACE2 compared to BA.5.…”
Section: Interaction Of Sars-cov-2 Variants Of Concern With Ace2mentioning
confidence: 99%
“…SARS-CoV-2 S protein mediates the virus-infected cell membrane fusion 10,11 . To quantitatively monitor the fusion kinetics between effector cells expressing S protein from eleven SARS-CoV-2 variants (including the previous VOCs and VOIs) and target cell membranes, we performed S protein-mediated membrane fusion assay in Calu-3/DSP1-7 cells 20,[22][23][24][25][26][27] . Although the Alpha, Beta, Gamma, Delta Lambda, Mu, and BA.5 S protein expression levels were lower than that of the B.1.1 S protein (harboring the D614G mutation) on the transfected HEK293 cell surface, the remaining S protein levels were comparable (Fig.…”
Section: S Protein Fusogenicity Of Eleven Sars-cov-2 Variantsmentioning
confidence: 99%
“…Next, we examined the correlation of S protein-mediated cell-free viral infection with S protein fusogenicity. We used HEK293T cells to produce HIV-1 virions pseudotyped with SARS-CoV-2 S protein carrying the C-terminal deletion of 19 amino acids (∆19CT), normalized by the p24 concentration, and measured viral infectivity as described previously [20][21][22][23][24]26,27,[29][30][31] . Our results revealed that the Delta and BA.5 S pseudoviral infectivity measured using the HOS-ACE2/TMPRSS2 system were significantly higher than that of the B.1.1 S pseudovirus while that of the Wuhan, Alpha, Beta, Lambda, Mu, BA.1 and BA.2 S pseudoviruses significantly decreased in HOS-ACE2/TMPRSS2 cells compared to B.1.1 (Fig.…”
Section: Correlation Of Sars-cov-2 S Pseudovirus Infectivity With S P...mentioning
confidence: 99%